Réponses

Meilleure réponse !
  • Utilisateur Brainly
2012-10-08T19:09:45+02:00

Coucou,

 

A = 7(20x - 5)

   = 7 * 20x + 7 * -5

   = 140x - 35

 

B = -4(-3x+12)

   = -4 * -3x + -4 * 12

    = 12x - 48

 

C = 2 + 3(xa-5)

    = 2 + 3* xa + 3 * -5

    = 2 + 3xa - 15

     = 3 xa - 13

 

D= (2 - 4a)(3-2b)

   = 2 * 3 + 2 * (-2b) +( -4a) * 3 + -4a * -2b

   = 6 - 4b -12a + 8ab

   

E = (5a + 1)(7+2b)

   = 5a * 7 + 5a * 2b + 1*7 + 1*2b

   = 35a + 10ab + 7 + 2b

 

 

Vérifie quand meme les calculs et j'espere que tu as compris